Comparison of oral toxicological properties of botulinum neurotoxin serotypes A and B - Cheng, Luisa W. (2011)
Botulinum neurotoxins (BoNTs) are among the most potent biological toxins for humans. Of the seven known serotypes (A-G) of BoNT, serotypes A, B and E cause most of the foodborne intoxications in humans. BoNTs in nature are associated with non-toxic accessory proteins known as neurotoxin-associated proteins (NAPs), forming large complexes that have been shown to play important roles in oral toxicity. Using mouse intraperitoneal and oral models of botulism, we determined the dose response to both BoNT/B holotoxin and complex toxins, and compared the toxicities of BoNT/B and BoNT/A complexes. Although serotype A and B complexes have similar NAP composition, BoNT/B formed larger-sized complexes, and was approximately 90 times more lethal in mouse oral intoxications than BoNT/A complexes. When normalized by mean lethal dose, mice orally treated with high doses of BoNT/B complex showed a delayed time-to-death when compared with mice treated with BoNT/A complex. Furthermore, we determined the effect of various food matrices on oral toxicity of BoNT/A and BoNT/B complexes. BoNT/B complexes showed lower oral bioavailability in liquid egg matrices when compared to BoNT/A complexes. In summary, our studies revealed several factors that can either enhance or reduce the toxicity and oral bioavailability of BoNTs. Dissecting the complexities of the different BoNT serotypes and their roles in foodborne botulism will lead to a better understanding of toxin biology and aid future food risk assessments.